A system and method for providing services in telemedicine application - A. Rasid, Mohd Fadlee; Saripan, M. Iqbal; K. Subramaniam, Shamala; Salman, Omar Hussein (2013)
The invention relates to a method for providing services comprising sending information detected or provided by at least one source (103) being at least a sensor and/or text message to a gateway device (102), wherein the sensor and gateway device (102) are positioned around the client (201); generating a request and priority code for service and at least one instruction based on the information by the gateway device (102); displaying the instruction on the gateway device (102) to be shown to the client; sending the request to a base station (101) through the gateway device (102); and assigning a suitable service by the base station (101) for the client (201) based on the request; wherein the gateway device (101) provides instruction as a form of advisory service to the client (201) even when there is no network connection for the request to be sent to the base station (101) by the gateway device (102) for the client to receive the service.